The effects of a muscle calcium sensitizer on exercise performance in male Sprague-Dawley rats - Davis, Robert T., III (Kansas State University, 2009)
Skeletal muscle fatigue has a complex multifaceted etiology in which the ability to regulate intracellular calcium concentration ([Ca[superscript]2+][subscript]i) and the myofibrillar response to elevated [Ca[superscript]2+][subscript]i are key components. Pertinent to this issue, a calcium sensitizer compound has been shown to increase contractile function via altered myofibrillar Ca[superscript]2+sensitivity in in-vitro preparations. We tested the hypothesis that a calcium sensitizer compound would increase the endurance capacity and VO[subscript]2peak in young male Sprague-Dawley rats above saline control values. The exercise tolerance test consisted of a progressive exercise test in which each rat initially ran at a speed of 25 m/min up a 10% grade for 15 min. Thereafter the treadmill speed was increased by 5m/min every 15 min until fatigue (i.e., the rat could no longer maintain pace with the treadmill). VO[subscript]2peak was determined according to previously established methods used in our laboratory. Each rat initially ran at 25 m/min up a 10% grade for 2-3 minutes. The speed of the treadmill was the increased progressively in a ramp-like manner until fatigue. VO[subscript]2peak was defined either as the point at which O[subscript]2 uptake did not further increase despite increases in treadmill speed or the highest VO[subscript]2peak prior to fatigue. A calcium sensitizing compound or saline was administered via gastric gavage. There was a significant increase (P<0.05) in endurance capacity with 10 mg/kg of the calcium sensitizer compound, but not at lower (0.5-5 mg/kg) or higher (20-40mg/kg) doses. This improvement in endurance capacity occurred in the absence of any changes in VO[subscript]2peak. The highest dose (40 mg/kg) produced a significant decrease (P<0.05) in the endurance capacity as well as VO[subscript]2peak. These data demonstrate that the in-vitro observations of increased [Ca[superscript]2+][subscript]i sensitivity and improved muscle function with a calcium sensitizing compound can translate to improved whole body exercise performance. Further studies need to be conducted to explore the efficacy of calcium sensitizing agents in animal models of chronic disease (i.e. CHF and diabetes). It is possible that a calcium sensitizer compound could be used as a potential ergogenic aid for patients whom enhanced physical capacity could be of significant therapeutic value, and lead to increases in activities of daily living and quality of life.
Keywords: Calcium; Performance; Exercise; Muscle; Physiology (0719)